Trends and factors associated with thinness among late adolescent girls in Ethiopia: Multivariate decomposition and multilevel analysis - Zemene, Melkamu Aderajew; Mengistu, Netsanet Worku; Nigatu, Solomon Gedlu (Frontiers in Nutrition, 2022)
Background: Undernutrition among adolescent girls is still a major public health problem in Low-and Middle-Income Countries (LMICs). Even though the global prevalence of thinness among adolescent girls declined over time, it remains steady in LMICs including Ethiopia. Therefore, this study aimed to assess the trends and factors associated with thinness. Methods: A logit-based multivariate decomposition analysis for a non-linear response model was fitted to identify factors that contributed to the change in thinness over time. For the associated factors, a multilevel binary logistic regression model was employed. The Intra-class Correlation Coefficient (ICC) and Likelihood Ratio (LR) test were used to assess the presence of the clustering effect, and deviance was used for model comparison. Statistical significance was declared at p-value< 0.05. Results: Thinness among late adolescent girls declined significantly from 34.4% [95% CI: 32.8%, 36.0%] in 2000 to 24.9% [95% CI: 23.4%, 26.5%] in 2016 with an annual average reduction rate of 1.73%. About 84% of the decrement in thinness was attributed to the change in the effect of the characteristics. Place of residence and marital status were significantly associated with a change in thinness due to coefficients change. The compositional changes in the age of the adolescents, religion, and types of toilet facilities were also significantly associated with the change in thinness. From the multilevel binary logistic regression, higher age of adolescents [AOR=0.83; 95% CI: 0.77,0.90], improved toilet facility [AOR=0.45; 95% CI: 0.31, 0.65], middle wealth index [AOR=1.45; 95% CI: 1.10,1.90], and female head of the household [AOR=0.77; 95% CI: 0.61, 0.98] were significantly associated at an individual level, whereas being from Somali [AOR=2.14; 95% CI:1.76, 3.10] and SNNP region [AOR=0.35; 95% CI: 0.18, 0.68] had a statistically significant association with thinness at community level. Conclusion: Thinness among late adolescent girls declined substantially, but it remains a major public health concern. Nutritional interventions targeting thinness reduction among late adolescent girls should base on the identified factors. Age, residence, marital status, type of toilet facility, religion, wealth index, sex of head of the household, and region were all associated with thinness in this study.